2008
DOI: 10.1111/j.1460-9568.2008.06465.x
|View full text |Cite
|
Sign up to set email alerts
|

Grueneberg ganglion neurons respond to cool ambient temperatures

Abstract: The Grueneberg ganglion (GG) - a neuronal cell cluster of unknown function localized to the vestibule of the anterior nasal cavity - is considered as a chemosensory compartment based on the expression of olfactory receptors and the olfactory marker protein. Axonal projection of GG neurons to so-called 'necklace glomeruli' in the olfactory bulb of the brain, which are thought to be important for suckling behaviour in rodent pups, has led to the hypothesis that the GG might be involved in mother/child interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 29 publications
(43 reference statements)
0
79
0
Order By: Relevance
“…As GGNs are ensheathed by glial cells and covered with keratinized epithelium BrechbĂŒhl et al, 2008;Liu et al, 2009) it has proven impracticable to obtain patch-clamp recordings from these neurons to this point (J. Weiss and F.Z., unpublished observations). As our findings provide direct evidence for a thermosensory role of GGNs they support and extend those of Mamasuew et al (2008) using c-Fos expression. But how can they be reconciled with the results of BrechbĂŒhl et al (2008)?…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As GGNs are ensheathed by glial cells and covered with keratinized epithelium BrechbĂŒhl et al, 2008;Liu et al, 2009) it has proven impracticable to obtain patch-clamp recordings from these neurons to this point (J. Weiss and F.Z., unpublished observations). As our findings provide direct evidence for a thermosensory role of GGNs they support and extend those of Mamasuew et al (2008) using c-Fos expression. But how can they be reconciled with the results of BrechbĂŒhl et al (2008)?…”
Section: Discussionmentioning
confidence: 53%
“…Thus far, only two studies have addressed this problem. Mamasuew et al (2008) used immediate early gene expression to suggest that the Grueneberg ganglion is activated by cool ambient temperature. By contrast, BrechbĂŒhl et al (2008), using cellular Ca 2Ï© imaging, found no evidence for temperature-induced responses in GGNs but were able to activate the cells with an as yet unidentified chemical that they collected during killing of mice with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Each cell sends out a single axon, and axons fasciculate immediately as they project caudally along the dorsal roof of the nasal cavity to the necklace complex in the olfactory bulb (24-26, 28, 29). The GG displays multimodal properties (21,(30)(31)(32)(33) and starts developing around embryonic day 16. Contrary to the other olfactory subsystems, the GG appears to be complete and functional at birth (24)(25)(26)(27)(28), ensuring immediate AP sensing and increasing chances of survival in the wild.…”
mentioning
confidence: 99%
“…7G), which was most visible in young pups (Ïœ3 d old). The Grueneberg ganglion, an olfactory organ capable of detecting alarm pheromones and cold temperatures (Mamasuew et al, 2008;Fleischer and Breer, 2010;Schmid et al, 2010), is located within the nasal cavity, and dissection of this ganglion revealed EGFP expression (Fig. 7G, right).…”
Section: Scn10a-egfp Micementioning
confidence: 99%